2009
DOI: 10.2319/121807-591.1
|View full text |Cite
|
Sign up to set email alerts
|

Class II Correction with the Cantilever Bite Jumper

Abstract: Objective: To identify the skeletal, dentoalveolar, and soft tissue changes that occur during Class II correction with the Cantilever Bite Jumper (CBJ). Materials and Methods: This prospective cephalometric study was conducted on 26 subjects with Class II division 1 malocclusion treated with the CBJ appliance. A comparison was made with 26 untreated subjects with Class II malocclusion. Lateral head films from before and after CBJ therapy were analyzed through conventional cephalometric and Johnston analyses. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
27

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 18 publications
(34 reference statements)
3
16
0
27
Order By: Relevance
“…18 This pattern has also been shown for the Herbst. 6,19 Leveling the Curve of Spee is another explanation, as it often flares the lower incisors. In a recent study 20 it was shown that lower incisors flare 4u for each millimeter of 'flattening' of the Curve of Spee.…”
Section: Discussionmentioning
confidence: 99%
“…18 This pattern has also been shown for the Herbst. 6,19 Leveling the Curve of Spee is another explanation, as it often flares the lower incisors. In a recent study 20 it was shown that lower incisors flare 4u for each millimeter of 'flattening' of the Curve of Spee.…”
Section: Discussionmentioning
confidence: 99%
“…2 Many different Herbst appliance designs have been reported in the literature. [3][4][5][6][7] Depending on the type of appliance that is used, different complications are more commonly reported. A few studies 2,8-10 have compared complication rates between different Herbst appliance designs.…”
Section: Introductionmentioning
confidence: 99%
“…These appliances promote mandibular protrusion with reciprocal distal forces in the maxillary arch. [3][4][5] Among these appliances, the Twin Force Bite Corrector (TFBC; Ortho Organizers Inc, Carlsbad, Calif) is a hybrid fixed functional appliance that has a plunger system combined with active push coils that deliver a constant force of approximately 210 g. 6,7 Consider that several successful reports of nonextraction Class II treatment are described in the orthodontic literature 3,6,8 using either fixed/removable and intra-or extraoral appliances to promote mandibular protrusion. Currently, a few studies 6,7 have been conducted to assess the dentoskeletal changes of the TFBC appliance, but none of these studies have evaluated the treatment effects of the TFBC appliance compared to a control sample.…”
Section: Introductionmentioning
confidence: 99%